Pendidikan Koperasi dalam Memahami Konsep Dasar Operasional Koperasi Syariah pada Koperasi Simpan Pinjam dan Pembiayaan Syariah Baitul Maal Wattamwil Forsitama Kabupaten Sleman Daerah Istimewa Yogyakarta - Sobarna, Nanang (LPPM Universitas Koperasi Indonesia, 2024)
Sharia cooperatives in carrying out operations must be in accordance with sharia principles, this is the basic operational concept for Sharia cooperatives so that every business carried out does not conflict with Sharia principles so that it brings blessings to cooperative managers, members, and the community. This is what administrators and managers of Sharia cooperatives need to understand, namely through cooperative education, one of which is organized by the Sharia Savings and Loans and Financing Cooperative (KSPPS) Baitul Maal Wattamwil (BMT) Forsitama, Sleman Regency, Yogyakarta Special Region. The aim of implementing this cooperative education is to provide an understanding of the basic operational concepts of sharia cooperatives for administrators and managers of KSPPS BMT Forsitama, Sleman Regency, Special Region of Yogyakarta so that they are able to increase knowledge for managing sharia cooperatives. The method used in cooperative education is the lecture method which is assisted by showing visual material, followed by questions and answers and discussions to solve problems that arise, accompanied by solutions. Through this cooperative education, the administrators and managers of KSPPS BMT Forsitama, Sleman Regency, Yogyakarta Special Region have been able to understand the basic operational concepts of sharia cooperatives, namely using contracts. musyarak muwafadhah with the principle of ta'awun or mutual cooperation which refers to the sources of Islamic Law (the Al-Qur'an and Hadith), the Fatwa of the National Sharia Council of the Indonesian Ulema Council and the laws and regulations in force in Indonesia.